Nucleophilic Reactions of The Bis Ammonium Salt of 4,4′,5,5′-Tetranitro-2,2′-biimidazole - Breiner, Megan M.; Chavez, David E.; Parrish, Damon A. (Synlett, 2013)
The reactivity of the bis ammonium salt of 4,4′,5,5′-tetranitro-1,1′-biimidazole toward nucleophilic addition to the electrophiles dimethylsulfate and mesitylene-O-sulfonyl hydroxylamine has been studied. We have found that the tetranitrobiimidazolate bis anion has sufficient nucleophilicity to react with these electrophiles to form new products, 1,1′-dimethyl-4,4′,5,5′-tetranitro-2,2′-biimidazole (DMTNBI), 1,1′-diamino-4,4′,5,5′-tetranitro-2,2′-biimidazole, and ammonium 1-amino-4,4′,5,5′-tetranitro-2,2′-biimidazolate. These materials were characterized chemically and with respect to their thermal stability.
Keywords: biimidazoles; heterocycles; N-amination; explosives; nitro compounds